THE EFFECT OF COMPENSATION ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE: Study on Employees of PDAM “Delta Tirta” Sidoarjo - Rachman, Mochammad Munir (jfpublisher, 2022)
Human resource in this era is important of its benefit because by the development of technology, it will force company side to accommodate the quality of labor as an essential requirement of labor (the employees) can be exploited as maximum for the efficacy of company, of course this matter relate to giving of compensation to employees. It is because employees compensation of company cannot fully improve activity of work that conducted to yield high achievement yet because the result did not influence by store; giving a bonus salary, main salary and also subvention as standard of work and also to the skilled person, therefore there is a need of consideration to company of including the role of companies head did not able to give compensation as a facility which will able to improve employee work performance and employees job satisfaction.